A Single-Center 18-Year Series of 73 Cases of Metaplastic Carcinoma of the Breast - Kassandra Thériault; Mariem Ben Moussa; Marjorie Perron; Christine Desbiens; Brigitte Poirier; Éric Poirier; Dominique Leblanc; Claudya Morin; Julie Lemieux; Jean-Charles Hogue; Dominique Boudreau (Hindawi-Wiley, 2024)
Aim. To examine the clinical management of metaplastic breast cancer (MeBC), particularly the role of chemotherapy. Methods. This retrospective study included patients with MeBC (n = 73) from a tertiary breast cancer center: the "Centre des Maladies du Sein of the CHU de Québec-Université Laval." The specimens were reviewed by two pathologists. Patient and tumor characteristics, systemic therapy (neoadjuvant and adjuvant), disease-free survival (DFS), and overall survival (OS) were recorded. Results. The median follow-up was 57.2 months. The mean tumor size was 39.5 ± 32.1 (range, 1-200) mm. Most were in grade 3 (75.3%), without evidence of clinical nodal involvement (75.3%), and triple-negative (79.5%). Chemotherapy was given to 49 (67.1%) patients. Thirty-seven patients (50.7%) underwent a mastectomy, and 22/37 (59.5%) received radiotherapy. Adjuvant chemotherapy was given to 36 patients (49.3%), and nine (12.3%) patients were treated with neoadjuvant chemotherapy. The 5-year OS and DFS rates were 60.2% and 66.8%. Among the nine patients who received neoadjuvant chemotherapy, three (33.3%) achieved a partial response, three (33.3%) had stable disease, and three (33.3%) had disease progression. The use of chemotherapy, especially in the adjuvant setting, had a significant positive effect on 5-year OS (P=0.003) and 5-year DFS (P=0.004). Nodal involvement was associated with worse OS (P=0.049) but similar DFS (P=0.157). Lumpectomy was associated with better 5-year OS (P<0.0001) and DFS (P=0.0002) compared with mastectomy. Conclusion. MeBC represents a rare heterogeneous group of malignancies with poor prognosis. Adjuvant chemotherapy was associated with improved OS and DFS. Patients should be carefully selected for neoadjuvant chemotherapy.